Annotated bibliography of the parthenogenetic marbled crayfish Procambarus virginalis , a new research model, potent invader and popular pet - Vogt, Günter (Zootaxa, 2018)
The marbled crayfish Procambarus virginalis is a new obligately parthenogenetic species that was detected in the mid-1990s in the German aquarium trade. Since then it has become a popular pet in many countries throughout the world and a valuable laboratory model for a broad range of biological disciplines. Releases have led to the establishment of wild populations in several European countries, Madagascar and probably Japan, making marbled crayfish an interesting paradigm of evolutionarily young and ongoing bioinvasions. This article provides an annotated bibliography of the scientific and popular scientific literature on marbled crayfish from its detection until today. Each reference is assigned to a publication format and one or more biological categories. The content is shortly described and its significance for marbled crayfish research and general biology is assessed. Of the 239 references listed 140 (58.6%) deal primarily with laboratory experiments on the biology of marbled crayfish and the establishment and use of marbled crayfish as a research model, 74 (31.0%) with its biogeography, invasions and ecology and 25 (10.4%) with hobby aquarist issues and the pet trade.
Gesehen am 27.03.2019